2022
DOI: 10.3390/polym14193976
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior of 3D Printed Polylactic Acid (PLA) Based Composites Reinforced with Natural Fiber

Abstract: Natural fiber-reinforced composite (NFRC) filaments for 3D printing were fabricated using polylactic acid (PLA) reinforced with 1–5 wt% henequen flour comprising particles with sizes between 90–250 μm. The flour was obtained from natural henequen fibers. NFRCs and pristine PLA specimens were printed with a 0° raster angle for tension tests. The results showed that the NFRCs’ measured density, porosity, and degree of crystallinity increased with flour content. The tensile tests showed that the NFRC Young’s modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 80 publications
4
22
0
Order By: Relevance
“…Polylactic acid (PLA) is another kind of 100% biodegradable polymer with a much higher strength than PBAT. Agaliotis et al [ 24 ] reported a new kind of natural fiber-reinforced composite (NFRC) filament fabricated using PLA reinforced with flour of henequen (a kind of plant) fibers. They studied the effect of the flour content on the tensile properties, including thermal, physical, and microscopic characteristics, where the specimen is manufactured by 3D printing [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polylactic acid (PLA) is another kind of 100% biodegradable polymer with a much higher strength than PBAT. Agaliotis et al [ 24 ] reported a new kind of natural fiber-reinforced composite (NFRC) filament fabricated using PLA reinforced with flour of henequen (a kind of plant) fibers. They studied the effect of the flour content on the tensile properties, including thermal, physical, and microscopic characteristics, where the specimen is manufactured by 3D printing [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agaliotis et al [ 24 ] reported a new kind of natural fiber-reinforced composite (NFRC) filament fabricated using PLA reinforced with flour of henequen (a kind of plant) fibers. They studied the effect of the flour content on the tensile properties, including thermal, physical, and microscopic characteristics, where the specimen is manufactured by 3D printing [ 24 ]. Additive manufacturing (3D printing) techniques are currently used to produce auxetic structures.…”
Section: Introductionmentioning
confidence: 99%
“…This result further demonstrated the excellent interlayer adhesion of these composites already observed during the 3D printing process. Lastly, the stiffness of these materials, which ranges from 1.6 to 1.8 GPa (Table S7), is comparable to the stiffness of PLA composites filled with natural fibers, which are among the most popular bio-based composites used in 3D printing.…”
Section: Resultsmentioning
confidence: 84%
“…Bright et al [ 8 ] mixed powdered raw and alkali-treated pineapple leaf fibers (PALF) with PLA and extruded the mixture as filament for 3D printing. Agaliotis et al [ 9 ] prepared henequen flour/PLA composite filaments by reinforcing PLA with 1–5 wt% henequen flour particles, and then printed samples with a 0° deposition angle. These FFF 3D-printed biocomposites have many advantages such as low cost, low density, acceptable specific mechanical properties, enhanced biodegradability, and recyclability.…”
Section: Introductionmentioning
confidence: 99%